Risk assessment of radiological dispersal device terrorism in Malaysia cities - Jamaludin, Amirul Fakhruddin; Omar Baki, Sharudin; Mansor, Ya’akob; Mohd Shah, Nurisya; Salled, Nurshariz Izham; Awang Kechik, Mohd Mustafa; Tahir, Dahlang; Abdul Karim, Muhammad Khalis (Semarak Ilmu Publishing, 2024)
Research has revealed that a terror attack in Malaysia, a developing nation, is a cause for alarm as it could create panic among its citizens. To address this, a study was conducted to investigate the dispersion of radionuclides after a hypothetical explosion, considering multiple cities in Malaysia as potential targets, including Kuala Lumpur, Kuching, and Kota Kinabalu. The primary aim of the research was to analyze the dose concentrations released from the RDD explosion over a 24-hour period and to assess the associated health risks in terms of morbidity and mortality per 100,000 people in these cities. The Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) software was employed to simulate the trajectory and dispersion of air particles, taking into account parameters such as time, altitude, and potential target cities, based on meteorological data from the Global Data Assimilation System (GDAS) of the National Oceanic and Atmospheric Administration (NOAA). The research focused on the analysis of Cs-137 at 50 TBq and was conducted with simulations on December 22, 2020. Results from the simulations revealed that the dose concentration in the air within 24 hours was 3.3 mSv, 1.8 mSv, and 7.7 mSv for Kuala Lumpur, Kuching, and Kota Kinabalu, respectively, while the dose deposited on the ground was 150 mSv, 71 mSv, and 310 mSv for the same cities. Furthermore, it was found that the dose concentration was most significant within the first four hours after the release of Cs-137, peaking between 30 to 90 minutes at altitudes of 60 to 80 meters. In terms of risk assessment, the research indicated that, for individuals located at this altitude during the timeframe of 0045 hours to 0100 hours after the dispersion of Cs-137, there could be 88 fatalities and 128 injuries per 100,000 residents in the city. The simulation offers valuable insights and guidance for governmental efforts to improve radioactive waste management and formulating or enhancing protocols to address such incidents promptly. It is essential to take swift and effective actions in order to protect the lives of the population in the event of a radiological terrorist threat.